High-efficiency phosphor-in-glass with ultra-high color rendering indexing for white laser diode lighting. Issue 2 (15th January 2022) - Zhang, Jiangdan; Wang, Liansheng; Xu, Fucai; Wang, Luhan; Xu, Li; Zhu, Qiangqiang; Liang, Xiaojuan; Xiang, Weidong
Abstract: Stable color converters exhibiting high color rendering index have drawn researchers' attention for their applications in high-quality white laser lighting. In this study, we develop the multi-color phosphor-in-glass (PIG) with the weight ratio of green-emitting (Y3 Al3.08 Ga1.92 O12 :Ce 3+ ) to red-emitting (CaAlSiN3 :Eu 2+ ) phosphor powders (10/1–18/1) by low temperature co-sintering method. The obtained composite material displays an outstanding optical and thermal performance, including a high internal quantum efficiency of 84.2%, a high transparency of 45% in the visible region and a low thermal quenching (it remains 86% at 448 K). By integrating 450 nm blue laser diodes with optimized multi-color PIG, the white light with a maximum luminous flux of 258 lm and a luminous efficiency of 137 lm/W is achieved for the first time. Additionally, considering the white balance, by tailoring the weight ratio of green-emitting to red-emitting phosphor and the thickness of PIG, the 14/1 PIG at fixed thickness of 0.75 mm produces pure white light with ultra-high color rendering index of 95.2 and a high luminous efficiency of 120.9 lm/W under power density of 2.39 W/mm 2 irradiation. The above superior characteristics imply that the multi-color PIG is an ideal candidate for high-quality white laser lighting applications.